Applied Algebra : Codes, Ciphers and Discrete Algorithms - Walker, Carol L.; Richman, Fred; Walker, Carol L. (Boca : Raton CRC Press, 2009)
sing mathematical tools from number theory and finite fields, Applied Algebra: Codes, Ciphers, and Discrete Algorithms, Second Edition presents practical methods for solving problems in data security and data integrity. It is designed for an applied algebra course for students who have had prior classes in abstract or linear algebra. While the content has been reworked and improved, this edition continues to cover many algorithms that arise in cryptography and error-control codes.
Includes Index 405-410p.
Keywords: Algebra; Discrete algorithms; Mathematics